The Influence of Work Discipline and Internal Communication on Employee Performance at PT Draco International - Andarsisi, Rosiana Andarsisi; Heriyanti; Larasati, Ayu; Faaroek, Safiani A (International Journal of Applied and Scientific Research, 2024)
Internal communication has an important role in the company to facilitate coordination so that employees are more productive at work and have a positive impact on the development of the company. Without communication, everything will not go well, resulting in miscommunication which will have a negative impact on individuals and companies. Work discipline in the company PT Draco Internasional has also not gone well because it is still free to enter the office so that a lot of work cannot be completed on time. This can be seen from the condition of frequent employees who are absent, arriving late which causes delays in delivery to customers with a predetermined time period. The purpose of this study was to determine the effect of work discipline and internal communication on the performance of PT Draco International employees. Research is quantitative positivism paradigm. The sample amounted to 50 respondents. The sampling technique is non-probability sampling with purposive sampling type. The results in this study indicate that internal communication has a significant influence on the performance of employees of PT Draco Internasional seen from the results of partial testing (t-test) with a significance value of 0.000 < 0.05. These results mean that internal communication factors including communication skills and the accuracy of selecting communication channels/media will result in satisfactory work.